A Mixed Ionic and Electronic Conducting Dual‐Phase Membrane with High Oxygen Permeability1. Issue 16 (23rd February 2015) - Fang, Wei; Liang, Fangyi; Cao, Zhengwen; Steinbach, Frank; Feldhoff, Armin
Abstract To combine good chemical stability and high oxygen permeability, a mixed ionic‐electronic conducting (MIEC) 75 wt % Ce0.85Gd0.1Cu0.05O2−δ‐25 wt % La0.6Ca0.4FeO3−δ (CGCO‐LCF) dual‐phase membrane based on a MIEC–MIEC composite has been developed. Copper doping into Ce0.9Gd0.1O2−δ (CGO) oxide enhances both ionic and electronic conductivity, which then leads to a change from ionic conduction to mixed conduction at elevated temperatures. For the first time we demonstrate that an intergranular film with 2–10 nm thickness containing Ce, Ca, Gd, La, and Fe has been formed between the CGCO grains in the CGCO‐LCF one‐pot dual‐phase membrane. A high oxygen permeation flux of 0.70 mL min−1 cm−2 is obtained by the CGCO‐LCF one‐pot dual‐phase membrane with 0.5 mm thickness at 950 °C using pure CO2 as the sweep gas, and the membrane shows excellent stability in the presence of CO2 even at lower temperatures (800 °C) during long‐term operation.